Towards a positive postnatal experience in Sub-Saharan African countries: the receipt of adequate services during the immediate postpartum period: a multilevel analysis - Habte, Aklilu; Tamene, Aiggan; Tesfaye, Legesse (Frontiers in Public Health, 2023)
Background Existing studies in the Sub-Saharan African (SSA) region have focused mainly on the frequency of postnatal visits, with little emphasis on the adequacy of care provided during visits. Hence, this study aimed to investigate the magnitude of receiving an adequate number of World Health Organization-recommended contents of care during the immediate postpartum visit, and its predictors in SSA countries. Methods The appended women file of the most recent (2016–2021) standardized Demographic and Health Survey report of eighteen Sub-Saharan African countries with a weighted sample of 56,673 women was used for the study. The influence of each predictor on the uptake of adequate postnatal care has been examined using multilevel mixed-effects logistic regression. Significant predictors were reported using the adjusted odds ratio (aOR) with their respective 95% confidence intervals (95% CI). Results The pooled prevalence of adequate postnatal care service uptake was found to be 42.94% (95% CI: 34.14, 49.13). Living in the southern sub-region (aOR = 3.08 95% CI: 2.50, 3.80), institutional delivery (aOR = 3.15; 95% CI: 2.90, 3.43), early initiation of ANC (aOR = 1.74; 95% CI: 1.45, 2.09), quality of antenatal care (aOR = 1.59; 95% CI: 1.42, 1.78), Caesarean delivery (aOR = 1.59; 95% CI: 1.42, 1.78), autonomy in decision-making (aOR = 1.30; 95% CI: 1.11, 1.39), high acceptance toward wife beating attitude (aOR = 0.83; 95% CI: 0.73, 0.94), and reading newspapers (aOR = 1.37; 95% CI: 1.21, 1.56) were identified as predictors of receiving adequate postnatal services during the immediate postpartum period. Conclusion The findings revealed low coverage of adequate postnatal care service uptake in the region. The Federal Ministry of Health and healthcare managers in each country should coordinate their efforts to develop interventions that promote women’s empowerment to enhance their autonomy in decision-making and to reduce attitudes towards wife beating. Healthcare providers ought to strive to provide skilled delivery services and early initiation of antenatal care.